Mitigasi Risiko Pada Rantai Pasok Bawang Merah (Allium ascalonicum L.) di Kabupaten Bantul, Daerah Istimewa Yogyakarta - Annisa, Warastra Nur; Guritno, Adi Djoko; -, Wagiman (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2021)
Shallot (Allium ascalonicum L.) is a horticultural commodity that has high economic value. The problems that occur in shallot commodities are easily damaged and rotten, easily experiencing shrinkage of scales, and fluctuating prices. Therefore, this study is aimed to identifying the shallot supply chain model and its risks, and then determining the appropriate mitigation for priority risks. The research method was carried out by purposive sampling and snowball sampling through in-depth interviews with the risk owner. Risk analysis is carried out using the ISO 31000:2009 standard and the risk priority is to determine by the value of the Risk Priority Number (RPN). The results showed that the shallot supply chain contained 19 models consisting of 6 tiers. The identified risks include 32 risks with 10 risks at avoid risk level, 2 risks at the transfer risk level, 17 risks at the level of managing risk, and 3 risks at the appetite risk level. Mitigation is carried out, namely at the farmer tier adding fumigation and blower in the warehouse, installing insect traps, applying advanced and simultaneous planting patterns, watering the plants before sunrise, spraying with fungicides and insecticides. In the slashing tier, you could pay onion to the farmer with a down payment and look for price information. In the tier of collectors, they applied advance payments, making sales records, and payment systems for fixed debts. At the tier sales, namely making records of sales, the system of payment of accounts payable for regular customers, and seeking information to the area available onion.